"Is CT Scan more Accurate than Endoscopy in Identifying Distance from the Anal Verge for Left Sided Colon Cancer? A Comparative Cohort Analysis". Issue 3 (15th March 2020) - Costi, Renato; , FACS; Ricco', Matteo; Negrini, Giulio; Wind, Philippe; Violi, Vincenzo; Le Bian, Alban Zarzavadjian
Abstract: Purposes : Accurately localizing colorectal cancer during surgery may be challenging due to intraoperative limitations. In the present study, localization of left-sided colon cancer (LCC) by CT scan is compared to colonoscopy. Material and methods : Consecutive patients with LCC located by colonoscopy and CT scan and undergoing left-hemicolectomy were included. Tumor distance from the anal verge (TDAV) was calculated by both CT-scan and colonoscopy, and then compared, using as reference TDAV measured intraoperatively. Statistical analysis was performed including (1) comparison of means between all three TDAVs, (2) comparison of mean differences between all three TDAVs, (3) comparison of number of patients with a difference between endoscopic TDAV and intraoperative TDAV ≤5 cm and the number of patients with a difference between CT scan TDAV and intraoperative TDAV ≤5 cm (4) statistical relationship between either CT scan and endoscopic and intraoperative TDAVs. Results : Both CT scan and endoscopy overestimate TDAV (25.8 ± 12.5 cm and 24.6 ± 10.6 cm vs. 21.5 ± 7.4 cm, p = 0.005), but CT scan TDAV resulted as being different from intraoperative TDAV ( p < 0.01). Regression analysis reported an increasing divergence of measurements with increasing values of intraoperative TDAV, which resulted greater for CT. Tumors within 5 cm of intraoperative TDAV were 22/28 (78.6%) for endoscopy, and 17/28 (60.7%) for CT ( p = 0.2448). Conclusions : Accuracy of both examinations seems poor, with a mean overestimation >3 cm and a significant number of tumors found at >5 cm from preoperative evaluation. Preoperative examinations' bias increase proportionally with TDAV length, decreasing their interest especially for tumors located at a greater distance from anal verge.